Exclusive breastfeeding behavior based on physical endurance and economic resilience of the family - Maharrani, Titi; Nugrahini, Evi Yunita; Junaedi, Mohammad Dwinanda; Pratami, Evi (International Journal of Public Health Science (IJPHS), 2024)
Breast milk is the best food for babies that can be given until the child is two years old or more, it is proven that breast milk has advantages that cannot be replaced by any food and drink because it contains the most appropriate, complete, and always adjusting nutrients with the baby's needs at all times. This study aimed to analyze the relationship between physical endurance and economic resilience of the family on exclusive breastfeeding behavior. This research was analytic research using a cross-sectional design. The sample of this research was 108 postpartum mothers who were taken by simple random sampling technique. The independent variables in this study were physical endurance and economic resilience, while the dependent variable was the behavior of exclusive breastfeeding. All data were collected using a questionnaire prepared by the researcher, and data were analyzed using a logistic regression test. Adequacy of food, housing ownership, and health insurance ownership are factors that influence exclusive breastfeeding behavior with a p-value <0.05. While 8 other indicators including nutritional adequacy, family health, resting place, income, income adequacy, children's educational ability, dropping out of school, and ownership of family savings do not affect exclusive breastfeeding behavior. Physical endurance relationship between the behavior of exclusive breastfeeding on the indicator of food adequacy and the factor of economic resilience affects the behavior of exclusive breastfeeding on the indicators of housing ownership and health insurance.